Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Topographic and Human-Pressure Interactions in Micro-Island Ecological Quality: A Geodetector-Based Framework from Jiangsu, China - Zijie Li; Shufen Guo; Dejin Zhang; Weichen Shi; Jialong Sun; Baozhang Chen (Journal of Marine Science and Engineering, 2026)
Island ecosystems are highly sensitive to climate change and intensive human activities. However, most existing assessments rely on subjective weighting and linear assumptions, which may not capture nonlinear temporal evolution and can be distorted by spatial-scale effects, including extreme density outliers on micro-islands. Focusing on five representative islands in Jiangsu Province, China (2014–2024), this study applies a data-driven evaluation framework. First, we constructed an Island Ecological Quality Index (IEQI) using principal component analysis (PCA) to integrate multidimensional ecological-state variables. Second, to reduce sensitivity to selected scale-related extremes in spatially restricted units, we employed a geographical detector model to identify explanatory factors and characterize interactive associations. The IEQI showed a nonlinear temporal trajectory, with fluctuations followed by recovery and stabilization after 2021. Under the robust adaptive Jenks classification, the factor detector showed high relative explanatory power for Artificial Shoreline Ratio (q = 0.8457), Population Density (q = 0.8339), Terrain Index (q = 0.8135), Tourist Density (q = 0.6282), and Built-up Ratio (q = 0.3189). Interaction analysis identified bi-factor enhancement between Terrain Index and Population Density (q = 0.8364) and nonlinear enhancement between Policy Count and Built-up Ratio (q = 0.6424). These q statistics describe spatial explanatory associations rather than causal effects. These findings challenge linear and generalized coastal management paradigms. We propose a “one island, one policy” framework that explicitly distinguishes micro-islands by their topographic buffering capacity and anthropogenic pressure profiles, enabling spatially targeted conservation and restoration strategies.

FengYuan: An End-to-End Global Weather Forecasting Model Driven by Multi-Source Observational Data - Zhaoming Liang; Yang Li; Yaqiang Wang; Yiheng Shi; Junming Chen; Fenghua Ling; Enda Zhu; Hai Wang; Lei Bai; Huabing Ke; Zhongyan Hu; Xiaoxu Liu; et al. (Journal of Meteorological Research, 2026)

Sustainable high-titer production of β-elemene in Yarrowia lipolytica via modular engineering, pathway refactoring, and a chimeric germacrene A synthase - Shun-Cheng Liu; Longxing Xu; Yuejia Sun; Lei Zhang; Weichen Zhang; Jing Xu; Pengcai Liu; Fan Shi; Faming Tian; Hong Xu; Xiaoming Song; Lijie Yuan; et al. (Chemical Engineering Journal, 2026)

A carbon-negative aerogel with superior CO₂ capture, flame retardancy, and strength based on a cellulose/MOF three-dimensional network - Huinan Wang; Lingling Zhu; Wenjie Xia; Mingdi Kang; Qianqian Zhou; Weichen Shi; Xinyi Xiang; Qingfeng Sun; Yingying Li (Chemical Engineering Journal, 2025)

Valorization of sewage sludge ash into sustainable porous geopolymer: Dual functions as supplementary foaming agent and precursor - Daquan Shi; Jiahe Miao; Yan Xia; Jian Wang; Fangyu Chen; Xiaobing Ma; Kunyang Yu; Chen Sun; Weichen Tian (Environmental Research, 2025)

Association Between Primary Dysmenorrhea and Mental Health Traits: A Study Based on Multi-Phenotype Correlation Network and Mendelian Randomization Analysis in Female College Students - Huiting Jiangzhou; Hanpeng Xu; Yanqin Wen; Zeyi Guan; Yang Zheng; Xuemin Jian; Weichen Song; Aamir Fahira; Jinmai Zhang; Qing Zhang; Ying Zhao; Manfei Zhang; et al. (Phenomics, 2025)

Two-dimensional nitrogen-doped carbon nanosheets-coated porous SiO composites sponges for durable anode materials of high-energy lithium-ion batteries - Zaohong Zhang; Weichen Chen; Jie Tian; Kai Zhang; Carlos Ponce de León Albarrán; Chuan Wu; Zhicong Shi; Zibiao Li; Jia Hong Pan (Chemical Engineering Journal, 2025)

Qualitative and quantitative detection of the quorum sensing signalling molecule autoinducer-2 in fermented milk based on 2,3-diaminonaphthalene derivatization - Hanyi Li; Zihang Shi; Xiankang Fan; Tao Zhang; Xiaoqun Zeng; Zhen Wu; Weichen Bao; Qiwei Du; Daodong Pan (Food Bioscience, 2025)

Exposure to 6PPD-Q induces dysfunctions of ovarian granulosa cells: Its potential role in PCOS - Hanxi Yu; Weichen Zhang; Danyun Wang; Biwei Shi; Yuhang Zhu; Weihuan Hu; Jiayi He; Jiawei Hong; Xiaolin Xu; Xiaoxiao Zheng; Wei Chen; Fangfang Wang; et al. (Journal of Hazardous Materials, 2025)

Tailoring the solvation shells of dual metal ions for high-performance aqueous zinc ion batteries - Xin Xu; Xiang Feng; Mingyan Li; Junyi Yin; Fuxiang Li; Jingzhe Chen; Weichen Shi; Yonghong Cheng; Jianhua Wang (Chemical Engineering Journal, 2023)

Different Turbulent Regimes and Vertical Turbulence Structures of the Urban Nocturnal Stable Boundary Layer - Yu Shi; Qingcun Zeng; Fei Hu; Weichen Ding; Zhe Zhang; Kang Zhang; Lei Liu (Advances in Atmospheric Sciences, 2023)

Impacts of Atmospheric Boundary Layer Vertical Structure on Haze Pollution Observed by Tethered Balloon and Lidar - Haijiong Sun; Yu Shi; Lei Liu; Weichen Ding; Zhe Zhang; Fei Hu (Journal of Meteorological Research, 2021)